Occupational characteristics and burnout syndrome in brazilian correctional staff - Oliveira, Raquel Lara Velez (2017)
Background: In the correctional context, occupational characteristics may contribute to the development of burnout. Objective: To compare the scores of Emotional Exhaustion (EE), Cynicism (CY) and Professional Efficacy (PE) of staff members according to occupational variables in two correctional facilities (CF1 and CF2). Methods: 339 Brazilian employees from two correctional facilities completed a socio-demographic/occupational questionnaire and the Maslach Burnout Inventory-General Survey (MBI-GS). The comparison between the scores obtained on each MBI-GS factor, according to variables of interest vs. correctional facilities, was performed using analysis of variance (ANOVA-two way: p < 0.05). Results: Statistically significant differences were observed between the levels of EE, CY and PE between the correctional facilities (p < 0.001); staff from CF2 presented worse levels. Women (p = 0.014) and individuals with a 10-year tenure or higher (p = 0.041) presented higher levels of EE. Lower scores of professional efficacy were found in CF2 staff members with a 10-year tenure or higher (p = 0.018). The prison escort and surveillance agents presented mean values of EE (p = 0.030) and CY (p = 0.008) that were significantly lower than those of the correctional security officers. Conclusions: The scores of EE, CY and PE of the staff members suffered a significant influence from the correctional facility, gender, professional category and tenure.